Draft Genome Sequence of Haemophilus haemolyticus Strain 16/010 O, Isolated from a Sputum Sample from a Cystic Fibrosis Patient - Fluit, Ad C. (Microbiol Resour Announc, 2019)
Haemophilus haemolyticus is considered a commensal of the respiratory tract that can cause opportunistic infections. It is closely related to Haemophilus influenzae. Here, we report the genome sequence of H. haemolyticus 16/010 O, which was isolated from sputum from a cystic fibrosis patient.